2016
DOI: 10.1007/s11695-016-2055-x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perception of Bariatric Surgery Among Primary Care Physicians: a Survey of Family Doctors in Ontario

Abstract: There appears to be a knowledge gap in understanding the role of bariatric surgery in the treatment of obesity. There is an opportunity to improve education and available resources for primary care physicians surrounding patient selection and follow-up care. This may improve access to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
73
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 12 publications
14
73
0
2
Order By: Relevance
“…Although a majority of healthcare providers in our study indicated utilizing referral services, the frequency of referral placement was scored as rarely or almost never despite the overwhelming evidence that bariatric surgery results in greater weight loss compared with all other interventions (41) and that a multidisciplinary approach to weight management is more effective (42)(43)(44). The findings of this study are consistent with other studies among non-OB/GYN providers demonstrating infrequent referrals (45,46). Physician-perceived lack of patient interest, patient refusal, increased operative fees, lack of confidence in bariatric surgery and lack of access to nearby bariatric centres have been cited as reasons for nonreferral (45,46).…”
Section: Discussionsupporting
confidence: 84%
“…Although a majority of healthcare providers in our study indicated utilizing referral services, the frequency of referral placement was scored as rarely or almost never despite the overwhelming evidence that bariatric surgery results in greater weight loss compared with all other interventions (41) and that a multidisciplinary approach to weight management is more effective (42)(43)(44). The findings of this study are consistent with other studies among non-OB/GYN providers demonstrating infrequent referrals (45,46). Physician-perceived lack of patient interest, patient refusal, increased operative fees, lack of confidence in bariatric surgery and lack of access to nearby bariatric centres have been cited as reasons for nonreferral (45,46).…”
Section: Discussionsupporting
confidence: 84%
“…Our current results show that physicians are almost always (99.5%) familiar with the possibility of surgical treatment of obesity, but only 166 (81.8%) respondents knew the indications for a bariatric operation. In the study published by Giaro et al the only surgical technique of treatment for obesity known by 39% of participating GPs was the gastric balloon implantation [20], and in the study by Auspitz et al only 23.8% of physicians felt comfortable explaining the procedure to the patient [24]. In our study 75.5% of physicians were able to explain to their patients how the bariatric operations are performed, and 69.8% of respondents could name the most commonly performed bariatric procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Tork et al published in 2015 results of a survey presented to primary care physicians which indicated that all respondents were aware of the benefits of bariatric surgery, including diminishing diabetes, hypertension and hyperlipidemia [21]. A publication by Auspitz et al showed that 48.1% of physicians responding to the survey support metabolic surgery for patients with diabetes [24]. Our results showed that the majority of respondents (96.6%) were aware that bariatric surgery is useful in the treatment of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations